Does workplace social capital predict care quality through job satisfaction and stress at the clinic? A prospective study - Hanne Berthelsen; Mikaela Owen; Hugo Westerlund (BMC, 2021)
Abstract Background Welfare societies like Sweden face challenges in balancing the budget while meeting the demand for good quality healthcare. The aim of this study was to analyse whether care quality, operationalized as survival of dental fillings, is predicted by workplace social capital and if this effect is direct or indirect (through stress and/or job satisfaction among staff at the clinic), controlling for patient demographics. Methods The prospective design includes A) work environment data from surveys of 75 general public dental clinics (aggregated data based on 872 individual ratings), and B) register-based survival of 9381dental fillings performed during a 3-month period around the time of the survey, and C) patient demographics (age, gender, income level and birth place). Using a multi-level discrete-time proportional hazard model, we tested whether clinic-level social capital, stress, and job satisfaction could predict tooth-level filling failure, controlling for patient demographics. One direct and two indirect pathways, moderated by filling tooth, location, and filling type, were tested. Results High workplace social capital reduced the risk of early failure of fillings in molar teeth, mediated by group-perceived job satisfaction (indirect path: OR = 0.93, p < .05, direct path from job satisfaction: OR = 0.89, p < .05). Contrary to expectations, we found no support for a direct effect from social capital on care quality or for the indirect pathway via stress at the clinic level. Conclusions Workplace social capital boosted the quality of dental fillings through increased levels of job satisfaction. In addition, staff at clinics with higher social capital reported less stress and higher levels of job satisfaction. These results indicate that promotion of social capital may improve both occupational health and care quality.